A Biomechanical Model of the Human Cornea - Núñez-Chongo, O.; Muñoz-Villaescusa, C.; Batista-Leyva, A. J. (Revista Cubana de Física; Vol 35 No 1 (2018), 2018)
Numerical modeling of human cornea has paramount importance to test in silica surgical procedures and to understand the effect on human eyes of injuries and other external aggressions. To prepare a numerical model that could reproduce correctly corneal behavior, it is necessary firstly to select a type of elastic material and its mechanical model of response. Then a numerical procedure must be implemented; normally FEM is used for calculations. It is then necessary to select geometry, create a mesh and calculate the elastic constants of the model. In the present contribution we create a model based in Mooney Rivlin hyperelasticity, with a mesh consisting in three layers and eleven elements per meridian from the apex to limbus. Two geometries were tested: cornea fixed by limbus and a second one formed by cornea, corneal limbus and part of sclera. We also prepared and tested the numerical procedure for establishing the stress free configuration.